Sinergitas Tugas dan Kewenangan Badan Keamanan Laut (Bakamla) dan Kesatuan Penjagaan Laut dan Pantai (KPLP) sebagai Coast Guard di Wilayah Yuridiksi Indonesia - Tampi, Robert Ronald (Neolectura, 2023)
This research aims to examine the lack of synergy between the Maritime Security Agency (Bakamla) and the Coast Guard and Coastal Guard Unit (KPLP) in law enforcement as Coast Guards in Indonesian waters. The research method used is normative juridical research with an explanatory approach, utilizing secondary data such as legislation, books, journals, and other legal sources. The research results indicate that the lack of synergy is due to differences in duties and authorities, as well as a lack of inter-agency integration in maritime law enforcement. Research recommendations include the development of maritime security patrol synergy, resolving regulatory overlaps, and strengthening inter-agency command integration to enhance national maritime security and support Indonesia's vision as a global maritime axis.